2013
DOI: 10.1063/1.4818478
|View full text |Cite
|
Sign up to set email alerts
|

Modeling electrical conductivity of nanocomposites by considering carbon nanotube deformation at nanotube junctions

Abstract: This paper investigates the effect of carbon nanotube (CNT) deformation on the electrical conductivity of CNT polymer composites at crossed nanotube junctions using a revised 3-dimensional CNT percolating network model. Two aspects of the work are considered. The first is concerned with the effect of CNT deformation on its intrinsic and contact resistances at CNT-CNT junctions. An analytical model based on electron ballistic tunneling theory and Landauer-Büttiker formula is proposed to describe the variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 49 publications
5
51
0
Order By: Relevance
“…[ 35,112,119,120 ] Recently, the validation of simulation results was remarkably improved by considering the deformation of CNT walls in the contact areas. [ 112,121 ] It was demonstrated that the increase of the contact resistance due to the increase of the intrinsic resistance of CNT cause by the wall deformation is signifi cant. Simulations indicated that the tunneling resistance change is the main mechanism of the piezoresistivity of CNTs-polymer nanocomposite strain sensors.…”
Section: Computational Analysismentioning
confidence: 99%
“…[ 35,112,119,120 ] Recently, the validation of simulation results was remarkably improved by considering the deformation of CNT walls in the contact areas. [ 112,121 ] It was demonstrated that the increase of the contact resistance due to the increase of the intrinsic resistance of CNT cause by the wall deformation is signifi cant. Simulations indicated that the tunneling resistance change is the main mechanism of the piezoresistivity of CNTs-polymer nanocomposite strain sensors.…”
Section: Computational Analysismentioning
confidence: 99%
“…With the above definitions, the intrinsic resistance along a deformed CNT between two nearest contact points j and k with the neighboring CNTs, as shown in figure 2(a), can be evaluated as, [25] ( ) ( )…”
Section: (B) and D' Vdw Is Thementioning
confidence: 99%
“…Thus, there is a minimum diameter D' min of the deformed CNT or a minimum distance d' vdw_min between CNTs [25]. The contact resistance at CNT junctions can be derived by the Landauer-Büttiker formula [24],…”
Section: (B) and D' Vdw Is Thementioning
confidence: 99%
See 2 more Smart Citations